On the Mechanism of Milling Induced Disordering in AlFe - Clavaguera-Mora, M. T. (1996)
The evolution of the B2-AlFe phase during mechanical grinding in Ar has been examined as a function of milling time by X-Ray diffraction, transmission Moessbauer spectroscopy and differential scanning calorimetry. Short and long range disorder was observed to increase with the mechanical treatment up to the attainment of a steady state. The evolution of the long range order parameter and of the local atomic configurations at Fe sites were analyzed in terms of possible mechanisms for milling induced disordering. The kinetics of the thermal reordering was studied under continuous heating and isothermal calorimetric regimes. Modeling of the reordering processes by diffusion controlled growth of pre-existing ordered grains is presented as well as the estimated values of both the enthalpy and the activation energy of the reordering process. The results are consistent with a nonuniform distribution of disorder throughout the sample and will be compared with preceding information on related systems.